PERSEPSI PETANI TERHADAP DIKLAT TEKNIS AGRIBISNIS PADI DI KABUPATEN LEBAK PROVINSI BANTEN - Achdiyat - (Jurnal Penyuluhan Pertanian, 2018)
ABSTRACT Large Agricultural Training Hall (BBPP) Agribusiness technical training was organized the valley of rice, corn and soybeans for farmers, in May of the year 2015 in Malingping BP3K and Wanasalam, Lebak Regency of Banten Province in unison with the mentoring Pajale phase I student high school agricultural extension of the Bogor regency of Lebak. Purnawidya 59 people, of that number there are only two the rest of the women as much as 57 people are male, 74,14% adults (34-52 years) 55,93% education, graduated JUNIOR HIGH SCHOOL â€“ SMA, 54.,% family dependents 2-3 persons, 59,32% of the old farming 8-12 years, 89.,83% have land category 0,13 ha, 8-9,47% and revenue was less than 30 million/year. Perception towards the main eye exercises are: 1) the system of Business Sustainability (81,36%), 2) Analysis of farming 76,27%), 3) marketing results (74,58%), and 4) work culture (74,58%), all of which fall into the category of medium, that purnawidya feel the benefits from the four the material that can be applied in the activities of usahataninya. The perception of eye exercises against the institution, namely: 1) harvest and Post-harvest rice (84.75%), 2) technology of rice cultivation (83.05%), 3) problem solving techniques (81,36%), 4) philosophy of PTT (76,27%), 5) tools and agricultural machinery (74,58), 6) Mitigation of climate (69,96%), enter in the category of being, that purnawidya feel the benefits of the next four such material referable farmers in usahataninya activities. The independent variable is the value of Chi-square (ï£2) = 40.55 Ho is rejected, there is a significant relationship or influence/keeratan between the main eye exercises and eye exercises support. Purnawidya feel any improvement: knowledge, skills, and attitudes in the field of cultivation/farming (particularly of rice) in the category of being. Keywords: perception, technical training, purnawidya ABSTRAK Balai Besar Pelatihan Pertanian (BBPP) Lembang menyelenggarakan Diklat Teknis Agribisnis Padi, Jagung dan Kedelai bagi Petani, pada bulan Mei tahun 2015 di BP3K Malingping dan Wanasalam, Kabupaten Lebak Provinsi Banten berbarengan dengan pendampingan Pajale tahap I mahasiswa Sekolah Tinggi Penyuluhan Pertanian Bogor di Kabupaten Lebak. Purnawidya 59 orang, dari jumlah tersebut hanya dua orang wanita selebihnya sebanyak 57 orang adalah pria, 74,14% dewasa (34-52 tahun), 55,93% berpendidikan tamat SMP-SMA, 54,24% memiliki tanggungan keluarga 2-3 orang, 59,32% lama berusahatani 8-12 tahun, 89,83% memiliki lahan kategori 0,1-3 ha, dan berpenghasilan 89,47% kurang dari 30 juta rupiah/tahun. Persepsi terhadap mata latihan utama yaitu: 1) Sistem Usaha Agribisnis (81,36%), 2) Analisa Usahatani 76,27%), 3) Pemasaran Hasil (74,58%), dan 4) Budaya Kerja (74,58%), semuanya masuk dalam kategori sedang, bahwa Purnawidya merasakan manfaat dari keempat materi tersebut yang selanjutnya dapat diterapkan dalam kegiatan usahataninya. Persepsi terhadap mata latihan penunjang yaitu: 1) Panen dan Pasca Panen Padi (84,75%), 2) Teknologi Budidaya Padi (83,05%), 3) Teknik Pemecahan Masalah (81,36%), 4) Filosofi PTT (76,27%), 5) Alat dan Mesin Pertanian (74,58%), 6) Mitigasi Iklim (69,96%), masuk dalam kategori sedang, bahwa Purnawidya merasakan manfaat dari keempat materi tersebut yang selanjutnya dapat dijadikan acuan petani dalam kegiatan usahataninya. Peubah independen nilai Chi-square (ï£2) = 40,55 Ho ditolak, berarti adanya kecenderungan yang nyata atau hubungan/pengaruh/keeratan antara mata latihan utama dan mata latihan penunjang. Purnawidya merasakan adanya peningkatan: pengetahuan, keterampilan, dan sikap dalam bidang budidaya/usahatani (khususnya padi) dalam kategori sedang. Kata kunci: persepsi, diklat teknis, purnawidya